Structural and Electrochemical Properties of Lutetium Bis-Octachloro-Phthalocyaninate Nanostructured Films. Application as Voltammetric Sensors - Alessio, P. [UNESP]; Apetrei, C.; Rubira, R. J. G. [UNESP]; Constantino, C. J. L. [UNESP]; Medina-Plaza, C.; De Saja, J. A.; Rodriguez-Mendez, M. L. (Amer Scientific Publishers, 2014)
Thin films of the bis[2,3,9,10,16,17,23,24-octachlorophthalocyaninate] lutetium(III) complex (LuPc2Cl32) have been prepared by the Langmuir-Blodgett and the Langmuir-Schaefer (LS) techniques. The influence of the chlorine substituents in the structure of the films and in their spectroscopic, electrochemical and sensing properties has been evaluated. The pi-A isotherms exhibit a monolayer stability greater than the observed in the unsubstituted analogue (LuPc2), being easily transferred to solid substrates, also in contrast to LuPc2. The LB and LS films present a linear growth forming stratified layers, monitored by UV-VIS absorption spectroscopy. The latter also revealed the presence of LuPc2Cl32 in the form of monomers and aggregates in both films. The FTIR data showed that the LuPc2Cl32 molecules present a non-preferential arrangement in both films. Monolayers of LB and LS were deposited onto 6 nm Ag island films to record surface-enhanced resonance Raman scattering (SERRS), leading to enhancement factors close to 2 x 10(3). Finally, LB and LS films deposited onto ITO glass have been successfully used as voltammetric sensors for the detection of catechol. The improved electroactivity of the LB and LS films has been confirmed by the reduction of the overpotential of the oxidation of catechol. The enhancement of the electrocatalytic effect observed in LB and LS films is the result of the nanostructured arrangement of the surface which increases the number of active sites. The sensors show a limit of detection in the range of 10(-5) mol/L.
Keywords: Chloro-Substituted Lutetium Bisphthalocyanine; Langmuir-Blodgett and Langmuir-Schaefer Films; Sensor; Catechol